Respostas

2014-03-17T21:02:50-03:00
Resposta

A

Equação original

S = So + Vt

S = Espaço final
So = Espaço inicial
V = Velocidade

Comparando as duas temos

S = 10 - 2t

So = 10m

B

V = -2m/s

C

S = 10 - 2t
S = 10 - 2.2
S = 10 - 4
S = 6m

D

S = 10 - 2t
90 = 10 - 2t
10 - 2t = 90
-2t = 90-10
-2t = 80
-t = 80/2
-t = 40
t = -40m

E

S = 10 - 2.2
S = 10 - 4
S = 6m

S = 6m
T = 2s

S (m)
|
|
|
|
|
|6-----------------------------
|                               |
|                               |
|                               |
|-------------------------------2------------------------------- T(s)